G150 Echocardiographic characteristics of neonates requiring inhaled Nitric Oxide (iNO). (27th April 2016) - Bailey, F; Wake, Z; Eckersley, L; Ramsay, J; Corrado, M; Bruce, D
Abstract : Aims: To identify echocardiographic indicators of persistent pulmonary hypertension (PPHN) in neonates requiring iNO in the first week of life and to determine the correlation with clinical outcomes. Following this, a standard echocardiogram protocol may be developed to improve future management and predict outcomes. Methods: A retrospective chart review of neonates with PPHN requiring iNO was conducted. Exclusion criteria included >5 days of age at commencement of iNO, <32 weeks gestation and significant cardiac anomalies. Cases were identified through neonatal database analysis from January 2010–June 2015. Demographic details, clinical information (diagnoses, ventilation requirements, iNO hours), supportive measures (inotropes, ECMO) and mortality were recorded. The initial echocardiogram performed on each patient was reviewed following a standard protocol. The measures recorded include atrial and ductal shunt, tricuspid regurgitation gradient and right ventricular function on visual assessment and ratio of the systolic/diastolic duration. Results: Eighty nine patients met inclusion criteria. The median gestational age was 39 weeks (range 32 to 43) and median birth weight 3345grams (range 2000 to 4800). Main diagnoses were: Meconium aspiration syndrome (34%), Hyaline Membrane Disease (24%) and perinatal asphyxia 16%). Patients received a median of 138 h (range 8–579 h) of ventilation and a median of 80 h (range 4–289 h) of iNO. HFOV was required in 37 (41.5%) cases. Inotropes were prescribed in 58 (65.2%) patients and ECMO in 4 (4.5%)cases; 12 (13.5%) patients died. An echocardiogram was performed in 80/89 neonates (90%) with 36/80 (45%) performed immediately prior to commencing iNO. Cases were divided into severe PPHN, 49 (55.1%) (defined as: iNO duration >100 hrs, multiple inotropes, ECMO) and non-severe for comparison as shown in the table, Table 2 . Conclusion: Acute neonatal PPHN remains a condition associated with high mortality. Severe cases were associated with severe RV dysfunction and R to L ductal shunting. Echocardiography should exclude underlying cardiac anomalies in neonates needing iNO and could further guide neonatal care. The latter could be enhanced and better studied with a standard echo reporting protocol.